Evaluation of the seismic performance of a caisson and an L-type quay wall - Yuksel, Y.; Yuksel, Z. T.; Cevik, E.; Orhan, K.; Berilgen, M. (ELSEVIER SCI LTD, 2017)
The damage caused by earthquakes in the past twenty years has revealed a generally high vulnerability of port structures. This fact, together with consideration of the economic importance of port structures, indicates the need for better seismic design approaches for berth structures and cargo handling facilities. In the recent decades, there have been many incidences of failure of gravity quay walls. These failures have stimulated great progress in the development of performance-based design methods. In this paper, several of these design approaches were studied experimentally and analytically. A series of shaking tank 1 g tests was performed using 1/15 scaled a caisson and an L-type quay wall with two different gravel backfill materials on firm sea bed conditions without liquefaction under different sinusoidal seismic loads. 1 g shaking tank tests were executed to verify the applicability of the sliding block concept and to estimate the performances of these quay wall types The shaking tank tests provided insight into the wall displacements and the dynamic thrusts by analyzing force components at the contact surface between the saturated gravel backfill soil and the wall.
Keywords: Earthquake; Quay wall; Seismic load; Newmark Sliding block method; Port engineering; BEHAVIOR; DEFORMATION; SHAKING; TESTS; Engineering; Geology